2004
DOI: 10.1093/glycob/cwh043
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-1 induces astrocyte differentiation, which leads to production of brain-derived neurotrophic factor

Abstract: Brain-derived neurotrophic factor (BDNF) is a neuroprotective polypeptide that is thought to be responsible for neuron proliferation, differentiation, and survival. An agent that enhances production of BDNF is expected to be useful for the treatment of neurodegenerative diseases. Here we report that galectin-1, a member of the family of beta-galactoside binding proteins, induces astrocyte differentiation and strongly inhibits astrocyte proliferation, and then the differentiated astrocytes greatly enhance their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 37 publications
1
46
1
Order By: Relevance
“…It has been reported that galectin-1 induces brain derived neurotrophic factor (BDNF) in astrocytes. 31 Furthermore, it was also reported that BDNF promotes adult neurogenesis. 3,32 Astrocytes expressing galectin-1 may thus increase the supply of such neurotrophic factors to promote neurogenesis after brain insults.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that galectin-1 induces brain derived neurotrophic factor (BDNF) in astrocytes. 31 Furthermore, it was also reported that BDNF promotes adult neurogenesis. 3,32 Astrocytes expressing galectin-1 may thus increase the supply of such neurotrophic factors to promote neurogenesis after brain insults.…”
Section: Discussionmentioning
confidence: 99%
“…There are several reports in the literature suggesting that astrocytes are capable of BDNF production in response to various stimuli (Miklic et al 2004;Sasaki et al 2004;Toyomoto et al 2004;Wu et al 2004;Aharoni et al 2005). One of these studies (Miklic et al 2004) reported the neutral effect of TNF-α on astroglial BDNF regulation.…”
Section: Discussionmentioning
confidence: 99%
“…2D) and TAs [18]. Together, these results [30,37] Schwan cells + [24,25] Migration after injury (Ox) [24,30] Red nucleus complex + [22] Cerebellum Neurons + + [26] Glial cells + + [26] Differentiation (R) [32] Forebrain Neurons + + [27] SVZ astrocytes + [18] Proliferation (R) [18] Olfactory bulb Sensory neurons + + + [28] Neurite growth and/or pathfinding (R) [31] Mitral cells + + [28] 2nd order projection neurons + [28] Interneurons + [28] Non neuronal cells + [29] 1256 M. Sakaguchi, Y. Imaizumi and H. Okano Galectin-1 in neural stem cells indicate that Gelectin-1 promotes the proliferation of adult NSCs.…”
Section: Galectin-1 Promotes the Proliferation Of Adult Nscsmentioning
confidence: 91%